Efeito da adição da mistura de própolis na dieta de novilhas nelore na qualidade de oócitos e produção in vitro de embriões - Oliveira, Fernanda Amarante Mendes de (2012)
The effect of food addition of propolis in the diet was evaluated on the oocytesquality and the embryo in vitro production. This study was carried out with the objective of evaluating the use of propolis and monensin on oocytes quality andembryos in vitro production of nellore heifers. Thirty-six heifers, at 24 months of age,were used, and distributed in a completely randomized experimental design with three treatments. The treatments consisted of a negative control group diet with no addition; agroup with addition of propolis and a positive control group with the food additive monensin. There was no effect of addition of propolis or the monensin on the number ofviable oocytes, embryos in vitro production (D7) and embryos hatched (D9). However,there was a higher number of total oocytes on propolis and control group compared tothe monensin group. But the results did not differ regarding the probability of the number of viable oocytes within the total oocytes retrieved. The addition of propolis inthe diet heifers' did not alter the reproductive features: improvement of oocytes qualityand increased embryos in vitro production.